If it's not what You are looking for type in the equation solver your own equation and let us solve it.
0.5(x+4)-(10x+9)=-65
We simplify the equation to the form, which is simple to understand
0.5(x+4)-(10x+9)=-65
Reorder the terms in parentheses
+( + 0.5x+2)-(10x+9)=-65
Remove unnecessary parentheses
+ 0.5x+2-(+10x+9+)=-65
Remove unnecessary parentheses
+ 0.5x+2-10x-9=-65
We move all terms containing x to the left and all other terms to the right.
+ 0.5x-10x=-65-2+9
We simplify left and right side of the equation.
-9.5x=-58
We divide both sides of the equation by -9.5 to get x.
x=6.10526315789
| -.5=4-4.5x | | 4x+(-3)=1 | | 11q=33 | | y=0.80(55)+136 | | 4x+(-3)=2 | | 8x-2=-9+7y | | .3(3x+6)=8x+10 | | 5(6+3x)=105 | | -5y+6=y+9 | | (-9-12)x=8-4x | | y=0.80(45)+136 | | 5x+-2x+5x=8 | | 20/(-4)=c | | x^2+x+30=0 | | .75x-1.25=-2 | | 64y^3-2=y-128y^2 | | 3h-15+h=5.2 | | y=0.80(35)+136 | | 3x-6=8(x-9) | | -10+3x=-2x+45 | | 8x-2=9+7y | | .20x+x=60 | | 3(x-1)-2=1/2(4x-8) | | (x+11)+(x+19)=16 | | y^2-36y-64=0 | | .6x+6.6=3.3 | | y^2-36y+64=0 | | m^3-121m=0 | | y=-0.80(25)+136 | | 14+2k-22=k | | -5y+4y+16=-56 | | 6+2(1x+-5)=2x+-4 |